RU’YAT AL-QAUMIYYAH FÏ SYI’RI MUDHAKKIRÄT ANDALUSIYYA LI NIZAR QABBANI - Khafid Roziki; Faisal Mahmoud Adam Ibrahim (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to describe the significance of the meaning of nationalism in the poem Mudhakkirät Andalusiyya by Nizar Qabbani and the factors that influence nationalism in the poem. In this study, the model used was library research. The material object in this research is a poem by Nizar Qabbani entitled Mudhakkirät Andalusiyya, written in Cordoba in 1955. This qualitative research is described descriptively using Roland Barthes' semiotic theory with a theory of significance order consisting of connotation and denotation. Sources of data in this study are in the form of words, phrases, and clauses derived from the poem Mudhakkirät Andalusiyya. Data collection techniques are reading techniques, translation techniques, and note-taking techniques. The data analysis technique uses data reduction techniques with close reading methods, data presentation, and conclusions. This research indicates that the poem Mudhakkirät Andalusiyya provides a perspective on the historical awareness of the Arabs as a ruling Spain and an overview of the contribution of the Arab nation and the Arabic language to Spain. The factors that influence Nizar Qabbani in the poem Mudhakkirät Andalusiyya are political factors, the unity of the Arabs, and the identity and history of the Arabs.